Harnessing the gut microbiome to modulate ferroptosis: a metabolic strategy for the treatment of digestive tract cancers - Wen, Jiexia; Liang, Huagang; Zhao, Min; Xuan, Bin; Meng, Xiangcai; Liu, Yang; Wang, Liwei; He, Li; Zhou, Tao; Tao, Yang; Wang, Yimin (Frontiers in Immunology, 2025)
Ferroptosis is a form of regulated cell death defined in recent years, characterized by iron-dependent accumulation of lipid peroxides. A large body of research has demonstrated that ferroptosis is closely associated with the progression of gastrointestinal tumors (such as gastric cancer, colorectal cancer, and esophageal cancer), and gastrointestinal tumor cells exhibit unique sensitivity to ferroptosis. This indicates that ferroptosis has emerged as a highly promising strategy to combat therapy-resistant colorectal cancer. Although the intrinsic ferroptosis-suppressive and ferroptosis-promoting pathways in gastrointestinal tumors have been fully elucidated, the current understanding of the extrinsic metabolites and pathways that regulate ferroptosis in the pathogenesis of gastrointestinal tumors remains relatively limited. Emerging studies have shown a strong link between gut microbial metabolism and the progression of gastrointestinal tumors. This review summarizes the relevant aspects of gut microbiota metabolism, explores how these gut microbiota-derived metabolites regulate cancer progression through ferroptosis, and proposes that targeting gut microbiota-mediated ferroptosis represents a potential therapeutic approach for gastrointestinal tumors.